Anti-inflammatory effects of animal plasma protein supplementation in mice undergoing simultaneous gut and lung inflammation. Issue 1 (1st January 2020) - Miró, L.; Amat, C.; Polo, J.; Moretó, M.; Pérez-Bosque, A.
ABSTRACT: We aimed to determine whether dietary supplementation with spray-dried porcine plasma (SDP) is effective in mice exposed to a dual S. aureus enterotoxin B (SEB) and lipopolysaccharide (LPS) challenges inducing simultaneous inflammation in the gut and lung. Male C57BL/6 mice were fed control or SDP-supplemented diets from weaning for 14 days. At the end of the experimental period, animals received LPS intranasal followed by SEB intraperitoneal doses. The dual challenge increased leukocyte recruitment into mesenteric lymph nodes and lung tissue, the percentage of activated monocytes and neutrophils, as well as the expression of Tnf-α, Ifn-γ and Il-1β in lung tissue and jejunal mucosa, while SDP attenuated these effects. Moreover, SDP augmented the expression of Il-10, Tgf-β and Foxp3 in these tissues. Supplementation with animal plasma proteins attenuated lung and intestinal inflammation provoked by simultaneous administration of LPS and SEB toxins and increased the expression of anti-inflammatory cytokines.